Targeted Therapy for Skeletal Muscle Fibrosis: Regulation of Myostatin, TGF-β, MMP, and TIMP to Maintain Extracellular Matrix Homeostasis - Dewi NM; Meiliana A; Defi IR; Amalia R; Sartika CR; Wijaya A; Barliana MI (Biologics: Targets & Therapy)
Nurrani Mustika Dewi,1,2 Anna Meiliana,2,3 Irma Ruslina Defi,4 Riezki Amalia,3,5 Cynthia Retna Sartika,6 Andi Wijaya,3,6 Melisa Intan Barliana1,5 1Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 2PT Prodia Widyahusada, Jakarta, Indonesia; 3Department of Pharmacology and Clinical Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jatinangor, Indonesia; 4Department of Physical Medicine and Rehabilitation, Hasan Sadikin General Hospital/Faculty of Medicine, Universitas Padjadjaran, Bandung, Indonesia; 5Center of Excellence for Pharmaceutical Care Innovation, Universitas Padjadjaran, Jatinangor, Indonesia; 6PT Prodia StemCell Indonesia, Jakarta, IndonesiaCorrespondence: Melisa Intan Barliana, Department of Biological Pharmacy, Faculty of Pharmacy, Universitas Padjadjaran, Jl. Ir. Soekarno KM 21, Jatinangor, 45363, Indonesia, Tel +6281214451177, Email melisa.barliana@unpad.ac.idAbstract: Muscle fibrosis, defined by the excessive deposition of extracellular matrix (ECM) components, is a key pathological process that hinders muscle regeneration following injury. Despite muscle’s inherent regenerative potential, severe or chronic injuries often result in fibrosis, which compromises muscle function and impedes healing. This review explores a range of therapeutic strategies aimed at modulating the molecular pathways involved in muscle fibrosis, with a focus on the inhibition of myostatin and transforming growth factor-β (TGF-β), as well as the regulation of matrix metalloproteinases (MMPs) and tissue inhibitors of metalloproteinases (TIMPs). Some therapy modalities, including physiotherapy and exercise therapy, which are commonly used, have demonstrated the ability to regulate extracellular matrix (ECM) components and promote muscle repair. In addition, the use of TGF-β inhibitors, herbal plants, and other biochemically relevant compounds, holds promise in controlling fibrosis by targeting key signaling pathways that drive ECM accumulation as well as having anti-fibrotic and anti-inflammatory properties. Regenerative medicine, including therapies using stem cell, secretome, and platelet-rich plasma (PRP), have also been used as single or adjuvant treatment for muscle fibrosis, and represents a novel and minimally invasive approach. Although these therapeutic strategies show considerable promise, translating preclinical findings to clinical practice remains challenging owing to variability in patient responses and the complexity of human muscle injuries. In conclusion, a multifaceted approach targeting ECM regulation, either as single treatment or combined treatment, offers a promising avenue for the treatment of muscle fibrosis.Keywords: muscle fibrosis, extracellular matrix, myostatin, TGF-β, MMP, TIMP